Risk-to buffer: Setting cyclical and structural banks capital requirements through stress tests - Cyril Couaillier; Valerio Scalone (European Central Bank (ECB), 2024)
In this paper, we propose a new framework to jointly calibrate cyclical and structural capital requirements. For this, we integrate a non-linear macroeconomic model and a stress test model. In the macroeconomic model, the severity of the scenarios depends on the level of cyclical risk. Risk-related scenarios are used as inputs for the stress test model. Banks' capital losses derived from a scenario based on a reference level of risk are used to set the structural requirement. Additional losses associated with the current risk scenario are used to set the cyclical requirement. This approach provides a transparent method to strike the balance between cyclical and structural requirements.
Keywords: C32; E51; E58; G01; 330; Financial vulnerability; macroprudential policy; non-linear models; capital requirements